PENGARUH NILAI, KEPUASAN, DAN INERSIA TERHADAP LOYALITAS PELANGGAN YANG BERBELANJA MELALUI E-COMMERCE PADA MAHASISWA FEB UNIVERSITAS ISLAM MALANG - Ahmad Fawaidur Rohman; N. Rachma; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis research was made with the intention of testing and analyzing the influence of value, satisfaction, and inertia on customer loyalty who shop through E-commerce case study research on Faculty of Economic and Business Universitas Islam Malang. Population and sample taken of 97 respondent by using saturated sample or census technique. Data collection is through with questionnaires. Data analyzing on this research helping with SPSS version 21. Data testing techniques on this research includes the validity test, reliability test, normality test, path analysis, MRA test, and test of research hypothesis. The result of analysis show that a) influential value significant to customer shopping loyalty in E-Commerce, b) influential value significant to shopping satisfaction in E-Commerce, c) shopping satisfaction have a significant effect to customer shopping loyalty in E-Commerce, d) satisfaction is not able to mediate the relationship between value to customer shopping loyalty in E-Commerce, e) inertia can moderate satisfaction with customer loyalty in E-Commerce.Keywords : Value, Satisfaction, Inertia, and Loyalty